The Urgency of Regulating Access to Pornography Content in Law No. 44 of 2008 concerning Pornography - Nynda Fatmawati Octarina; Muhammad Hasan (GoAcademica Research & Publishing, 2023)
Pornographic content is very troubling in the recent technological development, the impact of pornographic content has caused various kinds of negative things, one of which is addiction to pornographic content, this paper aims to answer the problems raised, namely related to the act of accessing pornographic content. The research method uses normative juridical by examining primary legal materials such as laws, as well as secondary legal materials such as books, journals and so on. The results of the study include an overview of whether the act of accessing falls into the category of pornography laws. The results of this study contain that it is appropriate for the act of accessing to be included in the category of pornography laws so that changes to the law are needed related to the act of accessing sexual content.